2014
DOI: 10.1111/age.12139
|View full text |Cite
|
Sign up to set email alerts
|

Novel Y‐chromosome polymorphisms in Chinese domestic yak

Abstract: Y-chromosome-specific haplotypes (Y-haplotypes) constructed using single nucleotide polymorphisms (Y-SNPs) in the MSY (male-specific region of the Y-chromosome) are valuable in population genetic studies. But sequence variants in the yak MSY region have been poorly characterized so far. In this study, we screened a total of 16 Y-chromosome-specific gene segments from the ZFY, SRY, UTY, USP9Y, AMELY and OFD1Y genes to identify Y-SNPs in domestic yaks. Six novel Y-SNPs distributed in the USP9Y (g.223C>T), UTY19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In Qinghai province, there are three yak breeds, including two indigenous breeds (Gaoyuan and Huanhu) and one improved breed (Datong). Currently, there have been few studies on Y-chromosome markers in the yak (Li et al, 2014). Previous genetic analyses indicated that INRA189 is a yak Y-chromosome-specific microsatellite (Y-STR), which has 2-3 alleles in partial Chinese yak populations and in the Swiss yak population (Han et al, 2000;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In Qinghai province, there are three yak breeds, including two indigenous breeds (Gaoyuan and Huanhu) and one improved breed (Datong). Currently, there have been few studies on Y-chromosome markers in the yak (Li et al, 2014). Previous genetic analyses indicated that INRA189 is a yak Y-chromosome-specific microsatellite (Y-STR), which has 2-3 alleles in partial Chinese yak populations and in the Swiss yak population (Han et al, 2000;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SRY4 , USP9Y , UTY19 , AMELY3 and OFD1Y10 markers; Li et al . ), we found four new Y‐SNPs mapped near the reverse primer region in the OFD1Y10 marker (g.569A>C, g.578A>C, g.608G>T and g.653G>C). All newly annotated sequences in this study were deposited in GenBank (accession nos.…”
mentioning
confidence: 72%
“…Based on six Y‐chromosome single nucleotide polymorphisms (Y‐SNPs), our previous study identified three Y‐haplotypes and two highly divergent lineages in 65 male yaks (Li et al . ). However, to the best of our knowledge, besides these reports, no information is available on the genetic diversity and phylogeographical distribution of yak Y‐chromosome haplotypes.…”
mentioning
confidence: 97%
See 2 more Smart Citations